Quantitative analysis of selected alkaloids of Mitragyna speciosa using 1H quantitative nuclear magnetic resonance spectroscopy - Garba, Suleiman Abubakar; Shaari, Khozirah; Abdul Manap, Mohd Rashidi; Lee, Soo Yee; Abdulazeez, Isah; Mohd Faudzi, Siti Munirah (John Wiley and Sons Ltd, 2024)
Mitragyna speciosa is a perennial plant native to Asia, well known for its psychoactive properties. Its major alkaloid mitragynine is known to have sedative and euphoric effects. Hence, the plant has been a subject of abuse, leading to addiction, necessitating efficient analytical methods to detect its psychoactive constituents. However, current chromatography-based methods for detecting the alkaloids are time consuming and costly. Quantitative nuclear magnetic resonance (qNMR) spectroscopy emerges as a promising alternative due to its nondestructive nature, structural insights, and short analysis time. Hence, a rapid and precise qNMR method was developed to quantify selected major psychoactive alkaloids in various parts of M. speciosa. Mitragynine, specioliatine, and speciogynine were quantified in relation to the integral value of the -OCH3 groups of the alkaloids and the internal standard 1,4-dinitrobenzene. The precision and reproducibility of the method gave a relative standard deviation (RSD) of 2%, demonstrating the reliability of the method. In addition, the method showed excellent specificity, sensitivity, high linearity range (R2 = 0.999), and limits of detection (LOD) and quantification (LOQ) values. The analysis revealed that the red-veined M. speciosa leaves contained higher levels of mitragynine (32.34 mg/g), specioliatine (16.84 mg/g) and speciogynine (7.69 mg/g) compared to the green-veined leaves, stem bark, or fruits.